IMPACT OF THE GOOD PRACTICES OF TRAINING IN THE DEVELOPMENT OF A COMMITMENT WITH THE ORGANIZATlON - Grueso Hinostroza, Merlín Patricia (Cuadernos de Administración, 2007)
Identify the predictive power that the implementation of a good practice for training has from the gender perspective in the development of the commitment with the organization, is the objective of this study. A survey was administered to 425 employees which consisted of a scale that measured the implementation of a good practice for training and development (Grueso, 2005) and a scale to measure the commitment to (he organization (Meyer & Allen, 1993). Based on the results of tbe study we concluded that the implementation of a good practice for training from the perspective of gender, incorporating an element of justice and allowing satisfaction of the needs of the employee, Promotes tbe development of the bonding oftbe employee to the organization; In the same way, the employee, upon receiving training with a purpose of development, generates a greater need to stay in the organization by the perception of a limited transferability of developed ski lis And the investment of time made in tbe process. Finally, the employee to perceive that the organization invests in him by developing training processes, feel indebted to the organization and develops a moral link with it.